2016
DOI: 10.1002/aenm.201601753
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Water Absorption by Molecular Design of Ionic Liquid Electrolyte for Li–Air Battery

Abstract: revealed that solvate ILs are suitable candidates for Li-S battery electrolytes because they greatly suppress the dissolution of lithium polysulfides [10] due to the formation of the complexes which can weaken the donor ability of the ethers. We have also studied solvate ILs as electrolytes for the Li-air battery. [11] Regarding the design of a future energy storage device based on the nonaqueous lithium-air system, a closed system using pure oxygen within a pressure vessel was proposed. However, an open syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 46 publications
0
14
0
1
Order By: Relevance
“…This battery showed reversible ORR and OER characteristics, analogous to that of batteries with aprotic electrolytes . A [Li(TEGDME(G4)) 1 ][TFSI] solvate IL showed quasireversible ORR and OER behavior and high oxidative stability up to 4.5 V versus Li/Li + . However, subsequent work revealed that the presence of water markedly deteriorated the reversibility of the Li–air battery.…”
Section: Ionic‐liquid Electrolytesmentioning
confidence: 78%
See 1 more Smart Citation
“…This battery showed reversible ORR and OER characteristics, analogous to that of batteries with aprotic electrolytes . A [Li(TEGDME(G4)) 1 ][TFSI] solvate IL showed quasireversible ORR and OER behavior and high oxidative stability up to 4.5 V versus Li/Li + . However, subsequent work revealed that the presence of water markedly deteriorated the reversibility of the Li–air battery.…”
Section: Ionic‐liquid Electrolytesmentioning
confidence: 78%
“…[140] A[ Li-(TEGDME(G4)) 1 ][TFSI] solvate IL showed quasireversible ORR and OER behavior and high oxidative stability up to 4.5 Vv ersus Li/Li + . [141] However,s ubsequent work revealed that the presence of water markedly deteriorated the reversibility of the Li-air battery.T op revent moisture intrusion from ambient air, several hydrophobic electrolytes were designed by mixing the solvate ILs with other hydrophobic ILs.The moisture content in the electrolyte exposed to ambient air was greatly suppressed and the reversibility of the Li-air battery was improved using this design. Adams et al [142] proposed an ew lithium ether derived chelate using a2 ,3-dimethyl-2,3-dimethoxybutane (DMDMB) complex with LiTFSI to form as table [(DMDMB) 2 Li]TFSI salt for use in Li-O 2 batteries.T his salt is compatible with Li anodes and its ether-based framework is more stable than simple glymes against O 2 À -initiated hydrogen abstraction.…”
Section: Solvate Ionic-liquid Electrolytesmentioning
confidence: 99%
“…Diese zeigte reversible ORR‐ und OER‐Eigenschaften, die analog zu denjenigen von Batterien mit aprotischen Elektrolyten waren . Die Solvat‐IL [Li(TEGDME(G4)) 1 ][TFSI] zeigte quasi‐reversibles ORR‐ und OER‐Verhalten und eine hohe Oxidationsstabilität von bis zu 4.5 V gegen Li/Li + . Allerdings ergaben die nachfolgenden Arbeiten, dass das Vorhandensein von Wasser die Reversibilität der Li‐Luft‐Batterie deutlich verschlechtert.…”
Section: Ionisch‐flüssige Elektrolyteunclassified
“…[ 58 ] Therefore, finding functional monomers and cross‐linkers that maintain protein activity has become a research hotspot in recent years. [ 59,60 ] Ionic liquids (ILs), usually composed of organic cations and inorganic or organic anions, are functional materials that exist in an ionic state at room temperature. [ 61,62 ] ILs have multiple interactions with template molecules, thereby making prepared imprinted materials have better thermal stability and structural adjustability.…”
Section: Synthesis Methods Of Protein Smipsmentioning
confidence: 99%